2008
DOI: 10.3109/2000-1967-216
|View full text |Cite
|
Sign up to set email alerts
|

Psychopathology and personality traits in patients with treated Wilson disease grouped according to gene mutations

Abstract: Wilson disease (WD) is a recessively inherited copper storage disorder mainly affecting liver and brain. Genotype/phenotype correlations have been report ed but as yet not regarding psychic symptoms. Our aim was to investigate if a correlation might exist between genotype and phenotype concerning psy cho pathology and/or personality traits in patients with treated WD. Nine homozygous and three compound heterozygous Swedish patients were retrospectively investigated, representing four different mutation set tin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…The study comprised 60 consecutive patients with WD recruited from the WD Clinical Research Program at the University of Belgrade who were clinically stable (no significant clinical change in the preceding 6 months) and had been on standardized therapy for WD for at least 2 years (ie, at the time of investigation, all patients were in a copper‐depleted state, as previously defined). 12 The diagnosis of WD was established by the following criteria: (1) history, (2) physical examination, (3) serum ceruloplasmin and copper levels, (4) 24‐hour urinary copper excretion, (5) liver biopsy, and (6) slit‐lamp ophthalmologic examination. 4 In 47 patients the diagnosis was confirmed by DNA analysis.…”
Section: Methodsmentioning
confidence: 99%
“…The study comprised 60 consecutive patients with WD recruited from the WD Clinical Research Program at the University of Belgrade who were clinically stable (no significant clinical change in the preceding 6 months) and had been on standardized therapy for WD for at least 2 years (ie, at the time of investigation, all patients were in a copper‐depleted state, as previously defined). 12 The diagnosis of WD was established by the following criteria: (1) history, (2) physical examination, (3) serum ceruloplasmin and copper levels, (4) 24‐hour urinary copper excretion, (5) liver biopsy, and (6) slit‐lamp ophthalmologic examination. 4 In 47 patients the diagnosis was confirmed by DNA analysis.…”
Section: Methodsmentioning
confidence: 99%
“…Finally, there is wide heterogeneity in the prevalence of psychiatric disorders in patients having WD, ranging from 4 to 47% for major depressive disorder and 1.4 to 11.3% for psychosis [ 88 ]. Interestingly, it has also been shown that some mutations in the ATP7B gene could be associated with specific psychopathological symptoms and personality traits [ 107 ]. For instance, patients who are homozygous for the Trp779Stop and the Thr977Met mutations had high scores on Psychopathy-related scales, whereas patients having His1069Gln/Arg1319Stop mutations had the lowest scores on these scales [ 107 ].…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, it has also been shown that some mutations in the ATP7B gene could be associated with specific psychopathological symptoms and personality traits [ 107 ]. For instance, patients who are homozygous for the Trp779Stop and the Thr977Met mutations had high scores on Psychopathy-related scales, whereas patients having His1069Gln/Arg1319Stop mutations had the lowest scores on these scales [ 107 ]. However, the evidence for the association of specific ATP7B gene variations with a specific pattern of psychopathology is, at best, preliminary.…”
Section: Resultsmentioning
confidence: 99%